2018
DOI: 10.1115/1.4039048
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tensile Response of Additively Manufactured Ti6Al4V With Embedded Spherical Pores

Abstract: The dynamic tensile response of additively manufactured (AM) dense and porous Ti6Al4V specimens was investigated under quasi-static and dynamic tension. The porous specimens contained single embedded spherical pores of different diameters. Such artificial spherical pores can mimic the behavior of realistic flaws in the material. It was found that beyond a certain pore diameter (Ø600 μm), the failure is determined according to the pore location, characterized by an abrupt failure and a significant decrease of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is not a surprise then, that with the emergence of additive manufacturing (AM) techniques, Ti-6Al-4V was one of the first metallic material to be incorporated into a commercial critical component [7]. Throughout the development of AM technology, Ti-6Al-4V was studied extensively in the scientific literature [8][9][10][11][12][13][14][15][16][17] as well as by aerospace and BioMed industries. Over the last decade, Ti-6Al-4V was intensively integrated into various additive manufacturing processes, demonstrating remarkable business case reasoning through improved functionality, efficient material usage, and cost reduction.…”
Section: Introductionmentioning
confidence: 99%
“…It is not a surprise then, that with the emergence of additive manufacturing (AM) techniques, Ti-6Al-4V was one of the first metallic material to be incorporated into a commercial critical component [7]. Throughout the development of AM technology, Ti-6Al-4V was studied extensively in the scientific literature [8][9][10][11][12][13][14][15][16][17] as well as by aerospace and BioMed industries. Over the last decade, Ti-6Al-4V was intensively integrated into various additive manufacturing processes, demonstrating remarkable business case reasoning through improved functionality, efficient material usage, and cost reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty samples are considered for analysis from the literature survey 10–17 as produced by different AM process methods. These AM processes include methods referred to as LPBF or SLM, wherein a laser is scanned in a select raster pattern to provide fusion of powders from a 20‐ to 100‐μm‐thick layer.…”
Section: Methodsmentioning
confidence: 99%
“…The Morris Jr. model was later developed to assess the mechanical behavior of drawn wires from Ti alloys 8 across a wide range of strain rate and to characterize the tensile behavior 9 of 316L LPBF AM material. A survey of the literature on Ti‐6Al‐4V AM material is now undertaken to explore the utility of this model to distinguish between the tensile behaviors of SLM and EBM materials 10–17 . Thirty examples are now selected that offer a representative sampling of alternative AM processing methods and postprocessing treatments which provide a wide range of tensile behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the pressureless microwave sintering, the mechanical properties of the components are affected by the presence of pores that are inevitable. Various research groups have evaluated the mechanical properties in the additive manufactured components [5][6][7]. Kumar et al [6] observed that ductility decreases with the increase of pore size in conventional sintering of the Ti6Al4V alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Chawla et al noticed that the tensile strength, Young's modulus, fatigue strength, and strain at failure improved with the decrease in pore size and pore densities in the sintering of steel [7]. Fadida et al observed that the presence of pores and their sizes influence the failure mechanism and mechanical properties of the parts produced by additive manufacturing processes [5].…”
Section: Introductionmentioning
confidence: 99%